Employment of refugees: a Malaysian perspective - Eishan Jan, Mohammad Naqib; Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (R.K.Sharma, Institute of Medico-Legal Publications, 2018)
Objective: This paper aims at identifying some challenges of the employment of refugees in enhancing the Malaysian economic growth. Analysis: The employment of refugees can be challenging to engage for the stakeholders if there is no efficient and proper legal framework to govern the human resources practices for this aspect as there is no legislation dealing with the employment of refugees in Malaysia. Method: In order to increase the productivity, the method used in existing refugees in the country can contribute as active work in the local workforce and thereby generate revenue for the government. Findings: It also explores whether developing a legal framework in order to allow and enforce the employment of refugees in Malaysia would be feasible. This study is primarily doctrinal and qualitative in nature. Result: The paper significantly contribute to some of the key focus areas in the Eleventh Malaysia Plan (2016-2020) such as improving labour productivity in the local economy, generating revenue for the government and promote human rights. Malaysia should create a legal framework for the employment of refugees to boost its fast booming economy.